The influence of Social Capital and Financial Capital on Innovation Strategies Furniture SMEs in Makassar - Jie Lydia Irawan; Lisa C Polimpung; Bartolomeus Tandiayu; Hendrikus Kadang; Bernadeth Tongli (IECON: International Economics and Business Conference, 2025)
The purpose of this paper is to understand the direct impact of social capital and financial capital on innovation strategies of furniture small and medium-sized enterprises (SMEs) in Makassar. Using resource-based view (RBV) theory, relationships among social capital theory, financial capital and innovation strategies were developed. Questionnaire-based survey was used to collect data from owners and senior managers of furniture companies. Data obtained were analyzed using descriptive analysis. The findings revealed that social capital have positive influence on innovation. Research limitations is that the study used perceptual measures of innovation strategies making it difficult to determine respondent bias. Practical implications is that manager or owner of furniture firms should initiate more social capital development as well as financial capital.